Faktor-Faktor yang Mempengaruhi Tax Avoidance pada Perusahaan Pertambangan BEI 2020-2022 - Dwimartha, Annisa Rizky; Aripratiwi, Ratna Anggraini; Junjunan, Mochammad Ilyas (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Muhammadiyah Riau, 2024)
This research aims to determine the factors that influence tax avoidance, as a result of the many tax avoidance practices. Factors that influence tax avoidance are debt equity ratio, return on asset, and return on equity. This research uses quantitative research methods, with the population being mining companies listed on the BEI in 2020-2022. The total sample was 28 companies using the purposive sampling method. The data analysis technique used is multiple linear regression with the E-views version 12 program. The results of the research show that only the debt equity ratio variable has an effect on tax avoidance, while return on asset and return on capital used have no effect on tax avoidance in mining companies listed on the IDX for the 2020-2022 period.